Income from Public Work Programmes and Household Economic Stability: Evidence from Mpwapwa District, Tanzania - Juma Mhina; Rehema Magesa; Baraka Msuya (The Indonesian Institute of Science and Technology Research, 2026)
Public Work Programmes (PWPs) are widely recognized as important instruments for poverty reduction and social protection, particularly in developing countries. This study examined the contribution of income from PWPs to household economic stability in Mpwapwa District, Tanzania. The research adopted a descriptive design, using both primary and secondary data sources. A sample of 300 household heads was selected through simple random sampling, while structured questionnaires and document reviews were employed to collect data. Descriptive statistics and multiple linear regression analysis were used to analyse the relationship between PWP participation and household economic outcomes. Regression results showed a strong association between participation in PWPs and household economic stability, with income diversification, employment creation, and local market contributions emerging as key determinants. Despite these benefits, income adequacy remained relatively low, suggesting that programme earnings were insufficient to fully meet household needs. This highlights the limitations of PWPs in providing long-term security without complementary interventions. The findings provide empirical evidence to guide policymakers in refining PWPs to better support vulnerable households while contributing to Tanzania’s development agenda and the Sustainable Development Goals.